Gender differences and multiple determinants of perceived physical and mental health in Italy - Golinelli, D.; Bucci, A.; Boetto, E.; Maietti, E.; Toscano, F.; Fantini, M. P. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Perceived health is largely dependent on multiple socio-demographic and behavioral lifestyles and healthcare related factors. This could be accentuated when gender is taken into account. The aim of this study is to explore gender-related differences in multiple socio-demographic and behavioral lifestyles and healthcare related factors associated with individual health status and to identify those responsible for changes in perceived physical and mental health among men and women in Italy. Study design. We conducted a cross-sectional retrospective study to investigate the association between multiple socio-demographic and behavioral lifestyles and healthcare related factors and individual health status of 99,479 adults in Italy, using data and information obtained from a nationwide survey. Methods. To identify the factors that correlate with the perceived physical and mental health status between males and females, we employed a censored regression analysis, a Tobit model, stratifying the analysis by gender. Results. Socio-demographic and behavioral lifestyles factors differently impact on males and females and this impact is stronger on perceived physical than mental health. The perceived physical and mental health status resulted better for men than for women. The integrated analysis of gender differences in sociodemographic and behavioral lifestyles and determinants of health revealed important inequalities, mainly related to citizenship and educational level, among the socio-demographic factors, and smoking habit and obesity, among the behavioral lifestyle factors. Conclusions. Gender imbalances mainly fall into inequality in social inclusion, educational level, and healthy lifestyle. This demonstrates how gender differences are still abundantly present in the modern Italian society. Such information should be taken into consideration by policy makers when interventions to improve the health and quality of life of the population are planned or evaluated.